KAJIAN STRATEGI PENGEMBANGAN AGROWISATA TAMAN HERBAL INSANI DI KECAMATAN BOJONGSARI KOTA DEPOK - Endah Djuwendah; Gunardi Yudawinata; Yayat Sukayat; Bintang Pinndito (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Indonesia is an agricultural country that relies on the agricultural sector. But the interest of the younger generation to work in this sector is diminishing. One alternative to overcome this is to develop the agricultural sector that is integrated with the tourism sector (agro-tourism). Taman Herbal Insani (THI) is an agrotourism that has the concept of quality and affordable herbal tourism education tour. The purpose of  research is to determine the potential attractiveness of THI agro-tourism and determine the THI agro-tourism development strategy. The research design used was descriptive qualitative with a case study approach. Data analysis uses analytical hierarchy process.  The results of this research show that the attraction of THI agro-tourism is diverse and has the potential to be developed : (1) natural attractions such as  landscapes of various types of medicinal plants and animals, cultural attractions in the form of gazebos with Sundanese cultural nuances, various traditional games and artificial attractions, namely swimming pools, spots photo selfie, playgrounds, fish ponds, camping ground. (2) Amenities in the form of learning opportunities to know the technical cultivation and processing of medicinal plants, swimming, camping, traditional fun games, family gatherings, selfie photos, buying plant seeds and herbal medicines, (3) accessibility to locations is very good asphalt roads through transportation modes general, (4) supporting facilities in the form of the availability of clean water infrastructure, electricity networks and the internet. The strategy for developing THI are done through improving the quality of management in the form of improving the quality of excellent services for tourists, maintaining and adding facilities and infrastructure, building a positive and informative image in promotion on social media and community empowerment by building official community management and development of herbal plants in the community